(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2016)
Plants have historically been used as a significant resource for healthcare. Curcuma caecia has reportedly been used in traditional medical systems for the treatment of a wide variety of diseases and conditions, including leucoderma, asthma, tumors, piles, bronchitis, and others. Bruises, contusions, and rheumatic pains can all benefit from applying the paste. Although the rhizomes and other plant components may be utilized medicinally, they are most often used to treat fever, cough, and asthma in adults and children. Antioxidant, antibacterial, antipyretic, larvicidal, insecticidal, antimicrobial, wound healing, and antihyperglycemic properties of curcuma caecia have all been the subject of scientific investigation. Aiming to provide a comprehensive overview of the research on its phytochemistry, traditional use, and medicinal investigations, this study aims to cover all the bases.Key-Words: Curcuma caecia, Phytochemistry, Traditional uses, Therapeutics